Orbitofrontal structural markers of negative affect in alcohol dependence and their associations with heavy relapse-risk at 6 months post-treatment - Zois, Evangelos; Vollstädt-Klein, Sabine; Kiefer, Falk (European psychiatry, 2017)
Background: Alcohol relapse is often occurring to regulate negative affect during withdrawal. On the neurobiological level, alcoholism is associated with gray matter (GM) abnormalities in regions that regulate emotional experience such as the orbitofrontal cortex (OFC). However, no study to our knowledge has investigated the neurobiological unpinning of affect in alcoholism at early withdrawal and the associations of OFC volume with long-term relapse risk. Methods: One hundred and eighty-two participants were included, 95 recently detoxified alcohol dependent patients (ADP) and 87 healthy controls (HC). We measured affective states using the positive and negative affect schedule (PANAS). We collected T1-weighted brain structural images and performed Voxel-based morphometry (VBM). Results: Findings revealed GM volume decrease in alcoholics in the prefrontal cortex (including medial OFC), anterior cingulate gyrus, and insula. GM volume in the medial OFC was positively associated with NA in the ADP group. Cox regression analysis predicted that risk to heavy relapse at 6 months increases with decreased GM volume in the medial OFC. Conclusions: Negative affect during alcohol withdrawal was positively associated with OFC volume. What is more, increased GM volume in the OFC also moderated risk to heavy relapse at 6 months. Reduced GM in the OFC poses as risk to recovery from alcohol dependence and provides valuable insights into transient negative affect states during withdrawal that can trigger relapse. Implications exist for therapeutic interventions signifying the OFC as a neurobiological marker to relapse and could explain the inability of ADP to regulate internal negative affective states.
Gesehen am 16.08.2018
Available online 12 August 2017